2023
DOI: 10.1001/jamanetworkopen.2023.43804
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and Long-Term Risk of Venous Thromboembolism

Eva Havers-Borgersen,
Jawad H. Butt,
Marianne Johansen
et al.

Abstract: ImportanceAs venous thromboembolism (VTE) remains one of the leading causes of maternal mortality, identifying women at increased risk of VTE is of great importance. Preeclampsia is a pregnancy-induced hypertensive disorder with generalized endothelial dysfunction. Some studies suggest that preeclampsia is associated with an increased risk of VTE, but much controversy exists.ObjectiveTo examine the association between preeclampsia and the risk of VTE during pregnancy, during the puerperium, and after the puerp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Most recently, in a nationwide cohort study in Denmark with 10.2 years median follow-up, a 43% elevated risk of VTE was observed among primiparous women with and without preeclampsia following adjustment [31]. A 2020 review by Hart et al reported a number of pregnancy-related factors that have been associated with VTE including preeclampsia (3-fold increase) [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most recently, in a nationwide cohort study in Denmark with 10.2 years median follow-up, a 43% elevated risk of VTE was observed among primiparous women with and without preeclampsia following adjustment [31]. A 2020 review by Hart et al reported a number of pregnancy-related factors that have been associated with VTE including preeclampsia (3-fold increase) [22].…”
Section: Discussionmentioning
confidence: 99%
“…History of VTE has been reported to increase the risk of preeclampsia 50% as well as other placenta-mediated pregnancy complications [23]. A biologically plausible mechanism for placenta-mediated complications including preeclampsia [24][25][26][27][28] and VTE could be thrombophilia or thrombosis [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact is useful because of the involvement of agents such as vitamin D, nuclear factor kappa B inhibitors and acetylsalicylic acid in the treatment of NETosis in preeclampsia [ 47 ]. Attention should also be paid to the fact that preeclampsia and arterial hypertension increase the risk of VTE in the course of pregnancy and the postpartum period and even in the 13 years after [ 48 , 49 ]. The aOR for the risk of VTE in these patients is 3.1 (95% CI 1.8–5.3) [ 32 ].…”
Section: Which Women Are “At Risk” and Why?mentioning
confidence: 99%